ANALISIS PROSPEK INDUSTRI PENGOLAHAN KERUPUK IKAN PATIN ”INTAN SARI” DI MARTAPURA, KABUPATEN BANJAR - Leila Ariyani Sofia (Fish Scientiae, 2019)
The purpose of this research is to determine: (1) the process of making fishcrackers catfish, (2) the level of profits and business efficiency, (3) the feasibility ofthe business, (4) marketing the product, (5) the level of weaknesses, strengths,opportunities, and threat (6) to improve their business prospects. The results of this research are (1) the process of making fish crackers weeding catfish consists of fish,to grind the fish meat, mixed, steaming, slicing, and drying, and packaging; (2) The profit in this business is IDR 1,213,011.00/year and the value of R/C ratio in the amount of 1.18; (3) fish cracker business finansal catfish are eligible to continue, withinvestment payback time is short (approximately 4 months); (4) distribution channelcatfish fish crackers by semi direct-marketing areas include Banjar District, Banjarmasin, Palangkaraya and Kapuas (Central Kalimantan), and Samarinda (East Kalimantan): (5) Management available on catfish fish cracker business is done by one person and assisted by subordinates for each part so that there is no fundamental dividing line between the various functions; (6) The results of the analysis of internal factors and external factors, which include: the addition ofproduction capacity, market expansion, service improvements, price competitive products, improvement of business management, and knowledge about consumer tastes.